2016
DOI: 10.1049/mnl.2015.0535
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation of quantum‐dot cellular automata logic gates

Abstract: Quantum-dot cellular automata (QCA) is a new paradigm in nanoelectronics, where binary information is represented by charge configuration in cells. Ideal QCA logic gates are thought to be dissipationless, since there is no intercell charge transfer and no current flows out of cells. This work presents that these gates dissipate energy and compare energy consumptions of conventional QCA logic gates in electrostatic and thermodynamic approaches. The results show that increasing the number of inputs, concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Recent studies show that although there is no electricity in QCA gates, these devices are not without energy loss [20]. The results show that the number of circuit inputs and the geometric compression in QCA are two very effective factors in energy loss [21]. All the proposed designs have been investigated at three tunneling levels 0.5EK, 1EK and 1.5EK at T=2ºK.…”
Section: Power Simulationsmentioning
confidence: 99%
“…Recent studies show that although there is no electricity in QCA gates, these devices are not without energy loss [20]. The results show that the number of circuit inputs and the geometric compression in QCA are two very effective factors in energy loss [21]. All the proposed designs have been investigated at three tunneling levels 0.5EK, 1EK and 1.5EK at T=2ºK.…”
Section: Power Simulationsmentioning
confidence: 99%
“…In this section, energy dissipation of common QCA gates; the 3MAJ, 5MAJ, INV, AOI, and the NNI are analysed. While the energy dissipations of these gates were roughly approximated in the previous research [13] by taking only two-time slots of one clock signal into account; in this paper, the four clock signals with eight time slots are considered to give a detailed picture of energy dissipation. Unlike thermodynamic calculations [13], which were based on the truth table of each gate, in the current research, states of all quantum cells of each gate are taken into account.…”
Section: Energy Dissipation Of Qca Logic Devicesmentioning
confidence: 99%
“…The change in the location of electric chargescauses a change in the electrostatic potential energy of the system. This changealso shows that some energy is gained or dissipated [13]. In a quantum mechanical approach, coherence vectorformalism can be used to estimate adiabatic power dissipation of a single QCAcell or a QCA wire [14].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…By assembling molecular cells in a proper manner, one can, in principle, create various electronic devices such as quantum wires, inverters, majority logic gates, and the integrated circuits. It has been demonstrated that the functional properties of molecular MV cells (e.g., cell–cell response) are closely related to the ET processes and the vibronic coupling. Recently, a number of organic and inorganic molecules have been proposed as promising candidates to act as molecular QCA cells. Further development of the field led to the progress in the understanding of the fundamental questions such as the power dissipation during a switching event due to interaction of the cell with the environment (thermal bath) and the effect of the applied time-varying electric field on switching, device latching, and power gain (see refs ). Contemporary achievements in the design and theoretical investigation of molecular QCA with the emphasis of MV realization were recently reviewed by Macrae in his exhaustive article …”
Section: Introductionmentioning
confidence: 99%